Technology Transfer Related Concepts - Irina Iulia SALANȚĂ; Ioana Natalia BELEIU; Alin MIHĂILĂ; Emil Lucian CRIȘAN (Revista de Management Comparat International)
Technology transfer is a fashionable term, a window towards improved processes, and also a huge part of business strategies meant to ensure competitive advantage, progress, and nonetheless, novelty for companies around the world. Due to its relevance and wide applicability, its associated concepts are even more important as they describe how technology transfer works and they also predict how technology transfer will evolve in the future. The purpose of this paper is to present the concepts used in association with technology transfer and consequently to surpass the shortcomings of existing research. Concepts as technology transfer, technology learning, diffusion of innovation, entrepreneurship, knowledge transfer, marketing of research are placed in the context of technology transfer, based on a detailed literature review that we have performed.